Answer :

The general form of the equation of a circle is:


(x - h)2 + (y - k)2 = r2


Where, (h, k) is the centre of the circle.


r is the radius of the circle.


Since, centre lies on Y - axis, it’s X - coordinate = 0, i.e.h = 0


Hence, (0, k) is the centre of the circle.


Substituting the given values in general form of the equation of a circle we get,


(3 - 0)2 + (2 - k)2 = 52


(3)2 + (2 - k)2 = 25


9 + (2 - k)2 = 25


(2 - k)2 = 25 - 9 = 16


Taking square root on both sides we get,


2 - k = ±4


2 - k = 4 & 2 - k = - 4


k = 2 - 4 & k = 2 + 4


k = - 2 & k = 6


Equation of circle when k = - 2 is:


x2 + (y + 2)2 = 25


Equation of circle when k = 6 is:


x2 + (y - 6)2 = 25


Ans: Equation of circle when k = - 2 is:


x2 + (y + 2)2 = 25


Equation of circle when k = 6 is:


x2 + (y - 6)2 = 25




Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

The equation of tRD Sharma - Mathematics

Find the eqRD Sharma - Mathematics

Find the eqRD Sharma - Mathematics

Show that tRD Sharma - Mathematics

If the circle x<sRD Sharma - Mathematics

Find the eqRD Sharma - Mathematics

Find the eqRD Sharma - Mathematics

The circle xRD Sharma - Mathematics

If the circles x<RD Sharma - Mathematics

If the centroid oRD Sharma - Mathematics